PLAY OF WORDS AS A MEANS OF CREATIVE THINKING VERBALIZATION IN LITERARY TEXTS - G. E. Markosyan; I. I. Lizenko (Гуманитарные и юридические исследования)
The article studies the most efficient ways of verbalizing creative thinking by means of actualizing the play of words in literary text. The operational determinant of a special style of texts aimed at verbalizing creative thinking is a set of language deviations which can be realized at all text levels and serve the material to study potential opportunities of language as a system and its representation in a verbal form as regards the author's outlook and reflective reality.